Norm scores of cancelation and bisection tests for unilateral spatial neglect: Data from a Brazilian population - Luvizutto, Gustavo José; Fogaroli, Marcelo Ortolani [UNESP]; Theotonio, Rodolfo Mazeto [UNESP]; Neto, Eduardo de Moura; Nunes, Hélio Rubens de Carvalho [UNESP]; Bazan, Rodrigo [UNESP] (Elsevier, 2020)
OBJECTIVE: Unilateral spatial neglect (USN) results in a consistent and exaggerated spatial asymmetry in the processing of information about the body or space due to an acquired brain injury. There are several USN tests for clinical diagnosis, but none of them are validated in Brazil. The aim was to obtain normative values from a healthy sample in Brazil and to evaluate the effects of demographic variables on USN tests. METHODS: This was a cross-sectional study performed with 150 neurologically healthy individuals. USN was evaluated using the line cancelation (LC), star cancelation (SC), and line bisection (LB) tests in the A3 (29.7 x 42.0 cm) sheet format. RESULTS: In LC, 143 participants had 0 omissions, and the occurrence of failure was significantly associated with aging (OR=1.1[1.02-1.2]; p=0.012). In SC, 145 participants had fewer than 1 omission, and the occurrence of failure was significantly associated with aging (OR=1.07[1.03-1.11]; po0.001). In LB, deviations were the lowest for those with the highest level of education (r=0.20; p=0.015), and the deviation was 9.5 mm. CONCLUSION: The cutoff points presented in this study may be indicative of USN, but due to performance differences based on age, we suggest using different norm scores for different age groups. These norm scores can be used in the clinic immediately for USN diagnosis.
Keywords: Diagnosis; Line Bisection Task; Line Cancelation Task; Standardization; Star Cancelation Task; Unilateral Spatial Neglect